HISTORICAL AND TECHNICAL ANALYSIS OF INSUFFICIENTLY KNOWN DESIGN FEATURES OF THE SHABOLOVKA RADIO TOWER - A V LEONOV (Structural Mechanics of Engineering Constructions and Buildings, 2015)
Virtual 3D modeling of the Shukhov's tower located in Shabolovka Street was performed in the S.I. Vavilov Institute for the History of Science and Technology of the Russian Acad- emy of Sciences in 2011-2013 and enabled to reveal a number of differences between histori- cal documentation and the real structure. Some of the results were published earlier. New re- sults regarding the height of the tower and the method of mounting of the intermediate rigidity rings to the outer legs of the two lower sections are presented in this article